PTH-086 Biological therapy in elderly onset ibd: sense, science and sensibility. (17th June 2017) - Miller, B; Crooks, B; Garr, W; Sorrentino, A; Scott, J; Nosegbe, U; Limdi, J
Abstract : Introduction: The role of biological therapies in the decisive induction and maintenance of remission of moderate-severe inflammatory bowel disease (IBD) is established through pivotal trials. There is a lack of data on their use in older patients. The primary aims of our study were to assess the efficacy and safety of biological therapies in older IBD patients at our institution. Method: We conducted a retrospective study of patients aged 60 and above with IBD treated with a biological agent at our institution. Data was collected using electronic case records and included demographics, disease characteristics (Montreal classification), treatment and adverse events. Results: Of 56 patients over the age of 60 who were treated with a biologic, 30 were diagnosed with IBD age 60 or over (range 60–84, median 66 years), 16 of whom were male. 15 patients had Crohn's disease (CD), 13 had a diagnosis of Ulcerative colitis (UC) and 2 had IBD unspecified. Median time to first biologic was 19 months (range 0–188). Median duration on biological therapy was 16 months (range 0.5–72 months). 50% of the patients were on concomitant immunomodulator therapy: 2 patients on methotrexate and 13 patients on azathioprine. Initial biological therapy was with infliximab (25 patients) or adalimumab (5 patients). Clinical response was noted in 25, partial response in 1 and 2 were primary non-responders. Data was not available for 2 patients. At 6 month follow-up, 21 patients showed continued clinical response to therapy, 1 showed a partial response and 1 patient had loss of response. 7 patients had loss of response at a later date (range 10–56 months). 9 patients required a switch in biological therapy to adalimumab (8) or vedolizumab (1). 6 patients demonstrated clinical response at 10 weeks, 2 patients had a partial response and 1 patient had no documented follow-up. 5 patients had major adverse events from biological therapy: 1 patient died due to cryptococcal meningitis, 3 patients required admission due to opportunistic infection and 1 patient required surgery for non-response to medical therapy. 10 patients suffered from minor adverse events due to biological therapy: infection not requiring hospital admission (4), infusion reaction to infliximab (2), basal cell carcinoma requiring excision (1), intolerance (1), arthralgia (1), transient neutropenia (1). Conclusion: Anti-TNF therapy may be effective in well-selected patients with elderly-onset IBD but may be associated with significant adverse effects. Real world safety and efficacy data are urgently needed to enable clinicians to make personalised but evidence-based decisions for considered and optimal management of older patients with IBD. Disclosure of Interest: None Declared